Usuwanie dwutlenku siarki z mieszanin gazowych drogą redukcji tlenkiem węgla - Bresińska, Iwona; Gąsiorek, Marek; Dudzik, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
The SO3 + CO reaction was proposed to remove sulfur dioxide from industrial outlet gases. This reaction allows to remove two toxic components (SO2 and CO) from the outlet gases. It was found that zeolite NaX is very efficient catalysts of SO2 + CO reaction. The main products of the reaction conducted at 440-500°C are: elemental sulfur and CO2. The formation of COS was also observed. The mechanism of the SO2 + CO reaction proceeding over NaX catalyst was formulated.
Keywords: dwutlenek siarki; redukcja tlenkiem węgla